2011
DOI: 10.2105/ajph.2010.194340
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Community-Based Processes for Research Ethics Review: A National Study

Abstract: Community-based processes for ethics review consider community-level ethical issues that institution-based IRBs often do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 21 publications
1
29
0
1
Order By: Relevance
“…There may be agencies that partner with the academic community or an advisory board constituted to oversee the project, but these bodies tend not to have the strong oversight consistent with that of a tribal government or government agency such as a health board. Certainly nonnative communities cannot duplicate the formal governing bodies of tribes, but there has been growing advocacy for community IRBs or research review boards by organizations such as the Community---Campus Partnerships for Health 21,22,32 and the current findings lend further support for this advocacy given the increase in protection and control for the community. However, nonnative communities have to weigh the benefit of formal governance with the costs to develop such governance.…”
Section: Discussionmentioning
confidence: 60%
“…There may be agencies that partner with the academic community or an advisory board constituted to oversee the project, but these bodies tend not to have the strong oversight consistent with that of a tribal government or government agency such as a health board. Certainly nonnative communities cannot duplicate the formal governing bodies of tribes, but there has been growing advocacy for community IRBs or research review boards by organizations such as the Community---Campus Partnerships for Health 21,22,32 and the current findings lend further support for this advocacy given the increase in protection and control for the community. However, nonnative communities have to weigh the benefit of formal governance with the costs to develop such governance.…”
Section: Discussionmentioning
confidence: 60%
“…IRBs are often housed within academic institutions or community institutions, such as hospitals [15], but some IRBs are corporate entities. In either case, community considerations are often missing from IRB deliberations [16,17], although IRBs are federally required to have community members and consider community concerns, according to Title 21 of the Code of Federal Regulations (CFR) [18]. Some IRBs do not fully assess community protections, consent, risks, or benefits, restricting their main focus to individual protections [16], and thus failing to incorporate another important ethical principle, respect for communities [19].…”
Section: Purpose and Ethical Principles Of Institutional Review Boardsmentioning
confidence: 99%
“…Community-based research shifts the traditional power dynamic, raising questions of equity, co-ownership of data, and mutual benefit. Shore et al's [16] study of community-engaged researchers' experiences with IRBs revealed that there is a need to expand the ethical analysis to include communitylevel considerations, which they posit is often missing in the IRB process.…”
Section: Evolution Of Community Ethics Reviewsmentioning
confidence: 99%
“…Communities benefit not only from using research to support progress but also from the opportunity for the "expression of self-determination" (57, p. 4). Their input can help researchers, as well as community organizations and private-sector partners, by generating data to inform program activities (72). Academic institutions can benefit from new partnerships between stakeholders and the popularity of community-centered programs and services (33).…”
Section: Community Engagementmentioning
confidence: 99%